O ensino de ciências no discurso dos professores: aproximações e distanciamentos com a literatura e os documentos oficiais - Bacri, Ana Paula Romero (2019)
The "Science Teaching" guides all the paths of this researcher and this research, so this study takes the term "Science Teaching" as a statement and analyzes it under the light of the Foucaultian Discourse Analysis. The thesis "The Teaching of Sciences in the Teachers' Discourse: Approaches and Distanciations", aims to investigate and reflect on the conceptions of Science Teaching that are present in the discourse of the professors of Science, in exercise, of the state network of education of a city of Minas Gerais. The voice of teachers is welcomed and echoes producing different meanings about the teaching they practice and in which they build their careers. The teaching of science needs a new perspective to look at, after all the data of the Organization for Economic Cooperation and Development presents data that indicate a crisis in the Education of Sciences. The low results obtained by our students in external evaluations, which do not improve over the years, distances Brazil from the goals established in the National Education Plan for the coming years. Thus, we see the need to think of Science Teaching based on the free and sincere speech of the teachers that make it happen inside the schools. The discourse of science teachers on their conceptions of teaching reveals discursive markers of their teaching posture, sometimes contradictory to official determinations. The research has as a place of investigation the school and the "Teaching of Sciences" as object of analysis. The research is a qualitative approach and we use the semi-structured interview as a resource for data collection. Thus, we chose a large school (Elementary School II and High School Basic Education) of each sector of the city, making a total of 5 participating schools. In each school, two teachers of Sciences were interviewed in Elementary School II, totaling 10 collaborating teachers. We used an interview script to guide the interviews, which were recorded and transcribed. The transcriptions were the basis for the organization of the teachers' statements in the Thematic Enunciative Series, according to Foucault's guidelines, in his book "Archeology of Knowledge". From this process, we obtain 11 Enunciative Series (Student, Contradictions, Control, Criticism to Teaching, Curiosity, Practices, Teaching, Previous Experiences, Resistance, Knowing Power, Subject Teacher). Next, we submitted the files of the Enunciative Series to the NVivo Plus software and identified the 30 most frequent words. From this, we established the Enunciative Nodes, which were analyzed each in its particularity and then the discursive network formed by them. In the discursive network, we privilege the analysis of the Enunciative Nodes of greater regularity in the discourse of the teachers. The discussion developed in the research is based on well-established authors of the area of Science Education and the theory and methodology defined by the work of Michel Foucault. The data led us to perceive a teacher subject who holds in his professional identity a series of contradictions, that suffers with the process of objectification and subjectivation to which it is submitted by the Educational device. Identification of a wide process of blame for the discourse of the lack, which goes from pointing out the lack of interest and commitment of the student in the studies to the lack of resources and support of the Education network. The various forms of resistance perceived in this research point to the distances of teachers towards legal determinations. The displacement of the role of the subject teacher in the process of teaching learning points to an identity crisis of this professional. Our teachers need to be heard and their sayings should be echoed by the educational system, including in research that is dedicated to thinking about its potentialities, so that the reforms occur based on the problems actually faced by our teachers, following their perspective, and thus personalizing the Brazilian Education.